Art of war - Machiavelli, Niccolò 1469-1527 (University of Chicago Press, 2003)
Niccolò Machiavelli's Art of War is one of the world's great classics of military and political theory. Praised by the finest military minds in history and said to have influenced no lesser lights than Frederick the Great and Napoleon, the Art of War is essential reading for anyone who wants to understand the history and theory of war in the West-and for readers of The Prince and Discourse on Livy who seek to explore more fully the connection between war and politics in Machiavelli's thought.